STRATEGIES TO IMPROVE THE QUALITY OF TEACHERS OF MADRASAH THROUGH SUSTAINABLE PROFESSIONAL TRAINING - Munawir; Mustopa; Mulyadi (International Journal of Teaching and Learning, 2024)
The number of teachers in Indonesia with teaching in schools including the madrasah needs to improve the competence and professional teachers through continuous professional training so that the quality of education in Indonesia is getting better. The research method undertaken in this study is literature by searching for literature that fits the context of the research. The results of the research showed that the implementation of sustainable professional training with a focus on improving the pedagogical and professional competence of teachers of Madrasah is essential for the quality of education to be increased and to improve the profession of such teachers it is recommended that provision of professional development programmes be carried out in a regular and fair manner, so that by increasing the competences of teaching teachers through sustained professional training, they are expected to provide better education and contribute to the development of the effective madrasah.